Ensino de História e mídia : análise de videoaulas no Youtube : um estudo de caso - Silva, Mauricio da (2021)
This research aimed to analyze the video classes produced by a popular YouTube channel among users of the platform. Suggesting the problem of whether these video classes would create a narrative about history, what historical narrative the channel presents, what historical perspective do they convey and why they are so popular with their audiences. The aim of the research was to problematize the videos produced by Débora Aladim’s YouTube channel. Considering video classes as an audiovisual source, we seek to reflect which elements of audiovisual language are important in the process of reading this type of source. The methodology was based on a qualitative analysis (FLICK, 2009) of this media, based on its language and context; we intend to establish a connection between studies and interpretations on cinema, audiovisual source and education. The investigative bases were based on the analysis of "media culture" by Douglas Kellner (2001), audiovisual and cinematography by Marcos Napolitano (2008), Rodrigo de Almeida Ferreira (2018), Marc Ferro (1992), Elizabeth Ellsworth (2001), among others, the notes and concepts that made it possible to discuss audiovisual language in history. The reading of this audiovisual, allows us to formulate the following considerations: the aesthetic elements, such as assembly, cuts, editing, music, camera positioning and framing, are closely related to the structures of the narrative displayed in the videos; they carry artifacts of globalized media culture. The videos of the said channel presented differences as to language, narrative and aesthetics, this is due to the production context, because part of the videos were made by youtuber when he was young of basic education and other videos were created as academic in history. From the analysis together with the considerations of Bittencourt (2008), which underlines the importance of articulating history teaching with new technologies and Guimarães assumptions (2012), which highlights the relevance in incorporating new languages into classroom practice, we have developed as a didactic-pedagogical product a "guide" for video class production, our goal will be to help educators/them produce their own videos and make use of YouTube to share their materials.